Comparison of the Efficacy of the Global Leadership Initiative on Malnutrition Criteria, Subjective Global Assessment, and Nutrition Risk Screening 2002 in Diagnosing Malnutrition and Predicting 5‐Year Mortality in Patients Hospitalized for Acute Illnesses. Issue 6 (28th September 2020) - Balci, Cafer; Bolayir, Başak; Eşme, Mert; Arik, Güneş; Kuyumcu, Mehmet Emin; Yeşil, Yusuf; Varan, Hacer Doğan; Kara, Özgür; Güngör, A. Evrim; Doğu, Burcu Balam; Cankurtaran, Mustafa; Halil, Meltem
Abstract: Background: The Global Leadership Initiative on Malnutrition (GLIM) has developed new criteria for diagnosing patients with malnutrition. The aims of this study were to investigate the prevalence of malnutrition according to the GLIM criteria, Subjective Global Assessment (SGA), and Nutrition Risk Screening 2002 (NRS‐2002) and their association with long‐term mortality in patients hospitalized for acute illnesses. Methods: A retrospective analysis was performed in a sample of 231 patients with different comorbidities hospitalized for acute illnesses in medical or surgical wards. Nutrition status was retrospectively assessed with GLIM criteria using patients' records at admission in addition to SGA and NRS‐2002. The agreement between the tools was calculated using κ statistics, and the association of malnutrition according to each tool and mortality were analyzed using Cox regression analysis. Results: The mean age of the patients was 62.2 ± 18.2 years, and 56.7% were women. The prevalence of malnutrition was 35.9% with GLIM criteria, 37.2% with SGA, and 38% with NRS‐2002. The agreement between tools was good (GLIM‐SGA, κ = 0.804; GLIM–NRS‐2002, κ = 0.784). During a median follow‐up period of 63.2 months, 79 deaths occurred. The sensitivity in predicting 5‐year mortality was 59.49%, 58.23%, and 58.23%, and specificity was 76.32%, 73.68%, and 72.37% for GLIM criteria, SGA, and NRS‐2002, respectively. After adjusting for confounders, GLIM criteria best predicted 5‐year mortality (hazard ratio, 3.09; 95% CI, 1.96–4.86; P < .001). Conclusions: Our findings support the effectiveness of GLIM in diagnosing malnutrition and predicting all‐cause mortality among patients hospitalized for acute illnesses.